Implementation of Augmented Reality as Information and Promotion Media on Dieng Tourism Area - Banu Nur Affan; Agus Suryanto; Arief Arfriandi (Universitas Lampung, 2018)
Information becomes necessary for tourists to get and improve the knowledge of tourism and their experiences about tourist destination. In Dieng tourism area, tourist information and promotional media has not been structured, as well as the need of media. The purpose of this research is produce Augmented Reality application that can visualize information of Dieng tourism, as interactive and interesting information, promotion tourism media. This research produces an android application which is used as information and promotion media of tourism in Dieng. Testing according to ISO 25010 with functional suitability got 100% suitability with Blackbox test, on portability aspect application successfully installed, update and uninstall on various smartphone environment, on performance efficiency aspect show average launch time is 1817 ms and also 0,22% CPU and 177,8 MB Memory usage. Results usability obtained SUS score 79.6 indicates the application get acceptable category to be used as information and tourism promotion media in Dieng.